Provided support, caregiver burden and well-being in partners of persons with spinal cord injury 5 years after discharge from first inpatient rehabilitation. Issue 5 (May 2018) - Scholten, Eline; Kieftenbelt, Anneroos; Hillebregt, Chantal; Groot, Sonja; Ketelaar, Marjolijn; Visser-Meily, Johanna; Post, Marcel
Abstract Study design Cross-sectional study. Objectives To describe type and regularity of support given by partners for individuals with paraplegia versus tetraplegia 5 years after discharge from first inpatient rehabilitation; to describe perceived caregiver burden, mental health and life satisfaction among partners; and to analyse determinants of perceived burden and the partner's mental health and life satisfaction. Setting The Netherlands. Methods Participants were partners of persons with spinal cord injury (SCI) 5 years after discharge from first inpatient rehabilitation (N = 67). Participants completed a self-report questionnaire. Provided support was assessed with an existing scale consisting of 25 activities for which partners could indicate how often they provide support to the patient. Caregiver burden was assessed with the Caregiver Strain Index. Mental health was measured with the Short-Form Health Survey 36 (mental health subscale), and life satisfaction was measured with the Life Satisfaction Questionnaire. Results Five years after inpatient rehabilitation, partners provided support with a large variety of activities. How often and in which activities partners provided support was associated with lesion level. About 43% of the partners experienced high levels of caregiver burden. Provided support was related to perceived burden (r S = 0.58) and life satisfaction (r S = −0.24), and burden was negatively related to mental health (r S = −0.47) and life satisfaction (r S = −0.67). Conclusions High levels of perceived burden among partners and the associations between higher burden with lower well-being show the importance to prevent caregiver overload in partners of individuals with SCI. Monitoring burden during regular rehabilitation visits may help to early detect burden.